Effects of energy supplementation and breed of sire on the reproductive performance of zel ewes and carcass quality of fattened lambs - Mohajer, Mokhtar (2011)
A series of experiments were conducted to examine the effect of supplementary dietary energy during pre-mating period and late pregnancy on the reproductive performance of Zel ewes mated to Zel or Shal rams, and their effects on the carcass quality of fattened lambs. In the first experiment, in a 2×2×2 factorial design experiment, 184 Zel ewes received diets containing 11.5 % crude protein, but with either 2.0 Mcal/kg metabolizable energy (ME), (NDE: normal dietary energy) or 2.3 Mcal/kg ME (HDE: high dietary energy) for 28 days before mating with either Zel or Shal rams. They were also treated with two levels of PMSG hormone, either 300 or 500 IU upon CIDR removal for estrus synchronization. Either Zel or Shal rams were exposed to the ewes at the rate of 1 ram: 10 ewes for 72 hours, 36 hours after the time of CIDR removal. Blood samples were collected from the ewes at the time of CIDR insertion, 7 days after CIDR insertion, at the time of CIDR withdrawal, 36 hours after CIDR withdrawal and 120 hours after ram introduction for FSH, insulin and progesterone analysis. Ewes on high dietary energy (flushing treatment) showed significantly higher (P<0.05) fertility,prolificacy, lambing rate and twinning rate compared to the NDE, 85.71 vs 79.34%, 132 vs 109, 113 vs 87% and twinning 32.05 vs 9.58%, respectively. The effect of PMSG (300 and 500 IU) showed a trend of increased fertility, 82.41 vs 82.60%, for prolificacy,132 vs 109%, for lambing rate, 113 vs 87%, and for twinning, 32.05 vs 9.58%, respectively, with increasing dosage of PMSG, but were not significant. However, the effect of sire breed was significant. Ewes bred with Shal rams showed higher fertility, prolificacy, lambing rate, and twinning rate. It was suggested that increasing energy before mating (flushing) and using Shal rams to fertilize Zel ewes would increase the reproductive performance of Zel ewes. In the second experiment, 184 Zel ewes were used in an experiment to examine the effect of increasing dietary energy of ewes during the last 8 weeks of pregnancy. Ewes were mated to either Zel or Shal rams and allowed to be on a NDE (11.5% CP and 2.1 Mcal /kg ME) for three months after weaning followed by either the NDE or a diet with 2.3 Mcal/kg ME (HDE) for 8 weeks before parturition. The results showed that the mortality rates of lambs borned to ewes fed on HDE diets were significantly lower than those fed the NDE. Increasing the energy level during the last 8 weeks before lambing increased lamb birth weight and weaning weight. Ewes mated to Shal rams bore lambs that were higher in birth weights, weaning weights and also mortality. The increase in mortality was probably due to difficult birth attributed to increased twinning rate and also lamb birth weight. The third experiment conducted were to examine the effect of energy level, sire breed, sex, duration of fattening on lamb performance and carcass quality. In 2 × 2 × 2 × 3 factorial design experiment 120 male and female lambs born from Zel ewes mated to Zel or Shal rams were selected and given diets containing 2.2 or 2.5 Mcal/kg ME. Equal number of male and female lambs were divided into three groups and fattened for 60, 80 or 100 days. At the end of each fattening period they slaughtered and carcass characteristics determined. The final live weights, average daily gain (ADG), hot carcass weight (HCW) of Zel lambs were significantly (P<0.05) lower than the crossbred (Zel × Shal) lambs. In general, the live weight, ADG and HCW of male lambs were higher (P<0.05) than those of female lambs, but these difference were not significant. Lambs fed HDE diets had higher (P<0.05) live weight, ADG and HCW than those of the NDE. As expected the live weight, ADG and HCW of lambs slaughtered at 60, 80 and 100 fattening duration were increased with increasing duration of fattening. Total bone, fat and meat carcasses of Zel lambs were significantly (P<0.05) lower than crossbred (Zel × Shal) lambs. From the results of this study it can be concluded that increased lamb production with improved lamb carcass characteristics can be achieved by increasing the energy level 3 weeks before mating to achieve high lambing rate and reduced mortality at birth. Increasing energy levels 8 weeks before parturition was also shown to improve lambing rate, twinning rate, increased lamb birth weight but may result in an increased mortality of lambs at birth. Zel ewes mating to Shal rams was produced bigger and heavier lambs at birth but may result in increased mortality due to difficult birth. Crossbred lambs show an increased rate of growth and higher carcass to liveweight ratio, and may be an option to increase lamb meat production on individual lamb basis. Also, it can be concluded that quality carcasses can be obtained by fattening crossbred lambs for duration of 80 days.